Teaching Fables in the Junior Grades of Primary School - Vidović, Ester; Reljac Fajs, Emilija (Revija za elementarno izobraževanje, 2015)
The aim of this paper is to explore the ways in which fables can help pupils in the junior grades of primary school develop their oral and written skills. It is written from a cognitive perspective within literary studies, focusing on a study of animal characters and morals in fables and researching the cognitive operations that result in hybrid animal characters. It also focuses on the universal character of morals, which can be viewed as an outcome of the process of conceptual integration. Addressing the universal nature of the main characters appearing in fables, as well as the universal issues expressed in their morals, the article looks at several possibilities for follow-up classroom activities. By devising extra activities aimed at developing their pupils‘ language skills, teachers of Croatian and English can motivate pupils to apply the topics in fables to everyday situations, thus encouraging them to develop their language skills as well as their capacity for judgement, character identification and value formation.
Keywords: fables; conceptual integration; language skills; moral; animal characters